How narrow-band and broad-band uvb irradiation influences the histomorphology evaluations of experimental animals' skin - a comparative study. Part I. - Katarzyna Borowska (Our Dermatology Online, 2017)
UVB phototherapy is an common and effective method of treating many skin diseases. The broad-band ultraviolet B (BB-UVB) spectrum is 290-320 nm. An alternative to this therapy is using the narrow-band ultraviolet B (NB-UVB). The aim of the study was to evaluate comparatively the influence of NB-UVB and BB-UVB phototherapy on the histomorphology (HM) of the skin of experimental animals. Both NB-UVB and BB-UVB phototherapy, result in microscopically observable changes in the epidermis and upper parts of the dermis papillary layer. No changes were observed, though, in the lower parts of the papillary layer or in the reticular layer of the dermis. The histological changes was more intense in the group exposed to BB-UVB radiation than in the NB-UVB group.